Kemampuan Menganalisis Teks Pidarta Bertema Pariwisata Budaya Siswa Kelas X SMKN 4 Denpasar Tahun Pelajaran 2023/2024 - Komang Ade Antara (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This study focuses on the ability to analyze the text of a speech on the theme of cultural tourism of class X students of SMK Negeri 4 Denpasar in the 2023/2024 academic year. The purpose of this study was to determine students' ability to analyze the text of a speech on the theme of cultural tourism in Balinese language learning at school. This type of research is descriptive. The methods used in this study are the research subject determination approach method, the research subject approach method, the data collection method, the test method, the observation method, the questionnaire method, the interview method, and the data processing method. The subjects of this study were class X students of SMK Negeri 4 Denpasar. The theory used is the theory of understanding analysis, types of analysis, understanding speech, types of speech, the structure of the speech text, and the theme of cultural tourism. The results of this study are the ability to analyze the text of a speech on the theme of cultural tourism of class X students of SMK Negeri 4 Denpasar in the 2023/2024 academic year is good. This is evident from the average score that has reached the Minimum Completion Criteria (KKM) of 88. It is known that out of 177 students studied, 104 students have met the Minimum Completion Criteria (KKM) with a percentage of 58.75% and 73 students have not met the Minimum Completion Criteria (KKM) with a percentage of 41.24%..